(untitled) (Research, Society and Development, 2022)
The region of the Submedio Vale do São Francisco, being the second largest producer of grapes, wines and grape juice in Brazil, has become relevant for economic development. It is also a large generator of waste. Thus, the present study aims to produce a coconut-type candy flavored with inferior quality grapes from the Juazeiro Agricultural Cooperative, located on the Juazeiro/Curaçá Highway at km 65. Four formulations of the candy were prepared, one without treatment (control), one and with treatment of 25%, 30%, and 50% of grape concentration, which were evaluated by 10 tasters, who judged the attributes: texture, aroma, flavor and global evaluation, through the 9-point Likert scale and the purchase intent of 3 points. The most accepted sample and the control sample were analyzed for moisture, carbohydrate, proteins, lipids, dietary fiber, ash and pH. It was evidenced that the treatment sample contained 25% of grapes, in which 70% of the tasters answered that they liked it very much in relation to the attributes texture (n=5), flavor (n=5), aroma (n=6) and global acceptance (n=5), already 60% purchase intention for would certainly buy for this same sample. Through physical-chemical analysis it was verified that the 25% grape sample contains 35.8% moisture, 42.7% carbohydrates, 1.8% proteins, 0.10% lipids, 18.5% dietary fiber, 0.6% ash and pH=4.2. In this way, the results obtained open up new perspectives for the use of inferior quality grapes and the elaboration of a functional sweet, since the sensorial characteristics evaluated were well accepted by the interviewees.